Patterns of Growth, Body Composition, and Lipid Profiles in a South African Cohort of Human Immunodeficiency Virus-Infected and Uninfected Children: A Cross-Sectional Study. (6th May 2017) - Ramteke, Sarah M; Shiau, Stephanie; Foca, Marc; Strehlau, Renate; Pinillos, Francoise; Patel, Faeezah; Violari, Avy; Liberty, Afaaf; Coovadia, Ashraf; Kuhn, Louise; Arpadi, Stephen M; ,
Abstract: Background: Prior research in sub-Saharan Africa reports dyslipidemia in perinatally human immunodeficiency virus (HIV)-infected children receiving ritonavir-boosted lopinavir (LPV/r) compared with efavirenz; however, interpretation of findings is limited by lack of comparison data from HIV-uninfected children. Methods: We conducted a cross-sectional analysis of lipid profiles and growth within a larger longitudinal cohort study of perinatally HIV-infected and HIV-uninfected children aged 4–9 years in Johannesburg, South Africa. At enrollment, anthropometrics, viral load, CD4, total cholesterol (TC), high-density lipoprotein, low-density lipoprotein (LDL), and triglycerides were measured. Weight-for-age Z-score (WAZ), height-for-age Z-score (HAZ), and body mass index-for-age Z-score (BAZ) were calculated. United States pediatric thresholds for dyslipidemia were used. Results: Five hundred fifty-three HIV-infected and 300 HIV-uninfected children (median age 6.9 years) of similar demographic characteristics were enrolled. Of the HIV-infected children, 94.8% were on combination antiretroviral therapy (cART) (65.4% on LPV/r- and 28.6% on efavirenz-based regimens). Among the treated, 94.3% had a viral load <200 copies/mL. Median CD4% was 34.4. The HIV-infected children had lower mean WAZ (−0.7 vs −0.3, P < .01) and HAZ (−1.1 vs −0.7, P < .01) compared with HIV-uninfected children. A lower proportion of HIV-infected children were overweight (BAZ >1) compared with HIV-uninfected children (14.4% vs 21.7%, P = .04). Whether on LPV/r or efavirenz, a higher proportion of HIV-infected children had borderline/elevated TC or abnormal triglycerides than HIV-uninfected children, although a higher proportion of those on LPV/r had borderline/elevated TC, borderline/elevated LDL, or abnormal triglycerides than those on efavirenz. Conclusions: In a South African cohort of HIV-infected children and population-appropriate HIV-uninfected children, unfavorable alterations in lipid profiles were detected in HIV-infected children regardless of treatment regimen compared with HIV-uninfected children. The HIV-infected children were of smaller size than HIV-uninfected children, but there was a high prevalence of overweight in both groups. Strategies for optimizing growth and early life management of lipid alterations may be warranted.